2020
DOI: 10.1038/s41541-020-00255-7
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal delivery of a multistage subunit vaccine promotes development of lung-resident memory T cells and affords interleukin-17-dependent protection against pulmonary tuberculosis

Abstract: The development of effective vaccines against bacterial lung infections requires the induction of protective, pathogen-specific immune responses without deleterious inflammation within the pulmonary environment. Here, we made use of a polysaccharide-adjuvanted vaccine approach to elicit resident pulmonary T cells to protect against aerosol Mycobacterium tuberculosis infection. Intratracheal administration of the multistage fusion protein CysVac2 and the delta-inulin adjuvant Advax™ (formulated with a TLR9 agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 46 publications
2
86
0
Order By: Relevance
“…Despite these differences, the level of protection conferred was equal across the different delivery methods ( 51 ). In a recent study, protection conferred by intra-tracheal administration of the fusion protein TB vaccine candidate, CysVac2, was associated with the induction of higher levels of antigen-specific CD4 + lung T RM , expressing IL-17, and RORγT ( 52 ).…”
Section: Adaptive Pulmonary Immunitymentioning
confidence: 99%
“…Despite these differences, the level of protection conferred was equal across the different delivery methods ( 51 ). In a recent study, protection conferred by intra-tracheal administration of the fusion protein TB vaccine candidate, CysVac2, was associated with the induction of higher levels of antigen-specific CD4 + lung T RM , expressing IL-17, and RORγT ( 52 ).…”
Section: Adaptive Pulmonary Immunitymentioning
confidence: 99%
“…14,15 In recent pre-clinical studies, it has been demonstrated that Advax as a mucosal adjuvant generates systemic and mucosal antibody responses and enhances T cell mediated responses. 13,16 There is increasing interest in delineating the exact mechanism of adjuvants in clinical use, for example by studying innate immune cell interactions with fluorescently-conjugated adjuvants. 17 While the dynamics of leucocyte responses to parenteral adjuvant administration have been characterised, there are few detailed analyses of innate immune cell recruitment, uptake and activation induced by pulmonary adjuvant candidates and greater understanding in this area is still required.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 In recent pre-clinical studies, it has been demonstrated that Advax as a mucosal adjuvant generates systemic and mucosal antibody responses and enhances T cell mediated responses. 13 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Advax is based on plant-derived inulin, a polysaccharide that when formulated into delta inulin particles and co-administered with subunit antigens, induces Ag-specific Th1, Th2 and Th17 T cell responses (10)(11)(12). Amongst its immunological effects, Advax TM induces a strong chemotactic effect, resulting in the recruitment of leukocytes to the site of vaccination, and engenders vaccine-induced protection against viral and bacterial pathogens (10)(11)(12)(13)(14)(15)(16)(17)(18). Advax has not been previously investigated in fungal vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Formulating Advax with TLR agonists enables additional modulation of T cell phenotypes, that may further enhance protective immunity. For example, formulation of the recombinant fusion protein, CysVac containing Ag85B and CysD, with Advax and the TLR9 agonist, CpG, drove an Ag-specific Th1 and Th17 cell response and provided superior protection against aerosol Mycobacterium tuberculosis infection(13).…”
Section: Introductionmentioning
confidence: 99%